YEZUPIL - Паньків, Б. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The intelligence deals with the history of Yezupil village in the Precarpathian region from the ancient times to the 80's of the last century. The article is based on archival sources, manuscripts and memoirs, periodicals and reference journals, which mention Yezupil. With the help of descriptive and statistical data the well-known historian Bohdan Mykhailovych Pankiv (1930-2015) tells about the various aspects of the life of the inhabitants of the village in XIV-XX centuries.